"You Cannot Get into My Taxi!" Perceptions of a COVID-19-based Rejection Episode Reported in the Newspapers. (October 2021) - Vacchini, Sabrina; Fasoli, Fabio; Volpato, Chiara
COVID-19-related incidents of xenophobia have hit the headlines. We asked participants to read about a rejection episode targeting a foreigner and we manipulated whether the rejection was motivated by COVID-19 fears or by no specific reasons. In the COVID-19 condition, the perpetrator was perceived as moral but as experiencing shame and guilt, while the target was seen as experiencing social pain. Helping intentions were predicted by either the perceived victim's social pain or morality and blame associated with the perpetrator.